2002
DOI: 10.1046/j.1365-2923.2002.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical students as standardized patients to assess interviewing skills for pain evaluation

Abstract: Medical students represent a readily accessible resource as patients for clinical simulations. Students tended to overestimate the performance of fellow students, but acting as a standardized patient had educational value, and can be used to extend simulated patient encounters within the curriculum. Further investigation is needed to improve the reliability of the feedback provided by student-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 12 publications
(17 reference statements)
0
31
1
Order By: Relevance
“…In fact, approximately 95% of medical schools in the United States currently use standardized patients and 85% use them as a component of student assessment Mavis, B. et al and Major, remarked that it was a challenge to replicate the complexities of clinical practice within a simulated environment [33,34]. This again highlights the challenges of using simulation effectively to enhance the learning experience.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, approximately 95% of medical schools in the United States currently use standardized patients and 85% use them as a component of student assessment Mavis, B. et al and Major, remarked that it was a challenge to replicate the complexities of clinical practice within a simulated environment [33,34]. This again highlights the challenges of using simulation effectively to enhance the learning experience.…”
Section: Resultsmentioning
confidence: 99%
“…Third, examiners noted that some SPs were unfamiliar with how much history to divulge or how to demonstrate physical exam findings. This suggests that sending written instructions and providing a brief orientation were insufficient in preparing first- and second-year students to be SPs in the MOSCE; implementing more formalized training similar to the 30-minute model used by Mavis, Ogle, Lovell, and Madden [10] may improve the consistency in SP performance in future iterations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review on peer-assessment in OSCEs found that using peer evaluators in an OSCE is appropriate in formative settings, promoting learning to all the students involved [9]. Though the literature on student SPs is less extensive, medical students have also been shown to be reliable and cost-effective SPs in formative OSCE settings [10]; furthermore, as with student examiners, Mavis and colleagues [11] reported that student SPs benefited from learning experiences gained during the OSCE encounter.…”
Section: Introductionmentioning
confidence: 99%
“…A final suggestion might be to consider peer evaluation. However, it has been reported that students generally overrate their colleagues and have a narrower range of marks than clinical teachers (Mavis et at., 2002).…”
Section: Discussionmentioning
confidence: 99%